Giuseppe Raddi (1770–1829): an Italian and Florentine naturalist, pioneer on Brazilian territory, his contribution to the knowledge of the Neotropical Flora and his legacy to the biodiversity of the third millennium. Issue 1 (2nd January 2018) - Baldini, Riccardo M.; Pignotti, Lia
Abstract: The life and work of the Italian naturalist Giuseppe Raddi is presented here, focusing on his contribution to the knowledge of Brazilian and, more generally, Neotropical flora. The most salient moments of his life at the turn of the eighteenth and nineteenth centuries are retraced, from his difficult youth, through his professional and scientific maturity, until the turning point in his life represented by the trip to Brazil and the discovery of Neotropical biodiversity. The period following his return from Brazil, when he was not permitted to study his own collections, is also explained, focusing on his tenacity in overcoming obstacles posed by some of his colleagues at the Natural History Museum in Florence. Although a complete retrieval of Raddi's botanical collections is difficult, mainly due to the dispersion and fragmentation of his herbarium, and though a significant part of the Brazilian material and taxa still waits for a modern analysis and interpretation, an assessment of his scientific legacy is here attempted. Finally, the role of the Neotropical historical botanical collections is highlighted as a tool of comparative knowledge of the tropics in the present-day context of big data analyses.